Detection of the elusive Dwarf sperm whale (Kogia sima) using environmental DNA at Malpelo island (Eastern Pacific, Colombia). Issue 7 (4th March 2021) - Juhel, Jean‐Baptiste; Marques, Virginie; Polanco Fernández, Andrea; Borrero‐Pérez, Giomar H.; Mutis Martinezguerra, Maria; Valentini, Alice; Dejean, Tony; Manel, Stéphanie; Loiseau, Nicolas; Velez, Laure; Hocdé, Régis; Letessier, Tom B.; et al.
Abstract: Monitoring large marine mammals is challenging due to their low abundances in general, an ability to move over large distances and wide geographical range sizes. The distribution of the pygmy ( Kogia breviceps ) and dwarf ( Kogia sima ) sperm whales is informed by relatively rare sightings, which does not permit accurate estimates of their distribution ranges. Hence, their conservation status has long remained Data Deficient (DD) in the Red list of the International Union for Conservation of Nature (IUCN), which prevent appropriate conservation measures. Environmental DNA (eDNA) metabarcoding uses DNA traces left by organisms in their environments to detect the presence of targeted taxon, and is here proved to be useful to increase our knowledge on the distribution of rare but emblematic megafauna. Retrieving eDNA from filtered surface water provides the first detection of the Dwarf sperm whale ( Kogia sima ) around the remote Malpelo island (Colombia). Environmental DNA collected during oceanic missions can generate better knowledge on rare but emblematic animals even in regions that are generally well sampled for other taxa. Abstract : Retrieving eDNA from filtered surface water provides the first detection of the Dwarf sperm whale ( Kogia sima ) around the remote Malpelo island (Colombia).